Coronary revascularisation for postischaemic heart failure: how myocardial viability affects survival. Issue 6 (1st December 1999) - Pagano, D; Lewis, M E; Townend, J N; Davies, P; Camici, P G; Bonser, R S
Abstract : OBJECTIVE: To assess the impact of revascularisation of viable myocardium on survival in patients with postischaemic heart failure. METHODS: 35 patients (mean (SD) age 58 (7) years) with severe heart failure (New York Heart Association (NYHA) functional class ⩾ III), mean left ventricular ejection fraction (LVEF) 24 (7)% (range 10–35%), and limited exercise capacity (peak oxygen consumption (VO 2 ) 15 (4) ml/kg/min) were studied. 21/35 patients had no angina. Myocardial viability was assessed with quantitative positron emission tomography and the glucose analogue 18 F-fluorodeoxyglucose (FDG) (viable segment = FDG uptake ⩾ 0.25 μmol/min/g) in all patients before coronary artery bypass grafting. Patients were divided into two groups: group 1, ⩾ 8 viable dysfunctional segments (mean 12 (2), range 8–15); and group 2, < 8 viable dysfunctional segments (mean 3.5 (3), range 0–7). The two groups were comparable for age, sex, NYHA class, LVEF, and peak VO 2 . RESULTS: Two patients died perioperatively and seven patients died during follow up (mean 33 (14) months). All deaths were from cardiac causes. Kaplan-Meyer survival analysis showed 86% survival for group 1 patients versus 57% for group 2 (p = 0.03). Analysis by Cox proportional hazard model revealed three independent factors for cardiac event free survival: presence of ⩾ 8 viable segments (p = 0.006); preoperative LVEF (p = 0.002); and patient age (p = 0.01). CONCLUSION: Revascularisation for postischaemic heart failure can be associated with good survival, which is critically dependent upon the amount of viable myocardium.